DESIGN AND BUILD AN AUTOMATIC TRASH RAKE TOOL IN FOR RIVER USING A CHAIN CONVEYOR - prayogo, wahyu; Santosa, Aa (Jurnal Mekanika dan Manufaktur, 2024)
Abstract Conveyor is a mechanical system that has the function of moving goods from one place to another. Conveyor is one of the many types of transportation used in the industrial world today. The aim of this research is to create a tool conveyor, which can help the community overcome problems in terms of handling waste in waterways and cleaning up floating rubbish in river basins, ditches and other waterways.This research uses research methodsand development with a quantitative approach. The results of making an automatic trash rake tool in the river using chain conveyor designed only one step of system work conveyor and the trash rake has a length of 1000 mm, width 500 mm, height 300 mm with a frame made of iron hollow. The power and power needed to rotate the tool is 216 watts ~ 0.216 Kw with a horsepower of 0.3 HP from a motor dynamo engine gearbox an AC type motor with a power of 0.37 Kw was selected; Power 0.5 HP. The linear speed of the chain every second can move as far as 0.12 m/s or 120 mm/s. The load acting on the chain has a waste carrying capacity of 1020 kg/hour or 0.28 kg/s with a tool effectiveness value of 99%. So this tool is working effectively.